Homogenized stress analysis in a dental implant system - Moon, HJ; Lee, JH; Choi, K; Choi, JB; Koh, CS (TAYLOR & FRANCIS LTD, 1997)
In this study, the stress state occurring at each trabeculae due to three different types of dental implant is investigated by a homogenization technique, in which the trabecular structure is assumed to be composed of repeating hexagonal units. This technique helps make a proper material model of bone and to analyse such a non-homogeneous structure at the level of an individual microstructural unit. Stress analyses with the homogenization technique show a much higher stress level in the sponge bone, compared to those with conventional FEM. It also shows that even a minor lateral force results in crucial stresses in the dental implant system. The stress states of the mandible with a hemisphere-rooted implant and a wedge type implant show similar levels, while those with a rectangular-rooted implant result in higher stresses. It is suggested that the distance between the implant tip and cortical bone be kept far enough apart to prevent stress concentrations in the mandible.